Efeitos da fotobiomodulação em modelos experimentais de queimaduras de terceiro grau: revisão sistemática - Ocon, Carlos Alberto (2017)
This systematic review was conducted to identify the role of photobiomodulation therapy in experimental models of third degree burns, the surveys were conducted in EMBASE, PUBMED and CINAHL databases, studies were searched from January 2007 to January 2017 in the area of third-degree burn photobiomodulation therapy. Animal models using photobiomodulation therapy for third degree burn treatment were included in the analysis. Twelve studies were selected from 136 original articles aimed at photobiomodulation therapy in third degree burn. Two independent evaluators with a structured tool to classify the articles critically evaluating the quality of the research. Although the small number of studies limits the findings, current literature indicates that photobiomodulation therapy may be an effective short-term approach to accelerate the healing process by increasing and modulating the inflammatory process, fibroblast proliferation, and increased collagen throughout the process. However, there is non- uniformity in the terminology used to describe the parameters and dose therapy to be used in photobiomodulation.